Research of Heat Rates Effect on the Process of Fuel-Bed Gasification of "Balakhtinskoe", "Osinnikovskoe", "Krasnogorskoe" and "Borodinskoe" Coal Deposits; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Zenkov A. V. Andrey Viktorovich; Yankovsky S. A. Stanislav Aleksandrovich; Matveeva A. A. Anastasiya Aleksandrovna; Lavrinenko S. V. Sergey Viktorovich; Gromov A. Aleksandr (2016, 2016)
Title screen